Open Partial Horizontal Laryngectomy as a Conservative Salvage Treatment for Laser-Recurrent Laryngeal Cancer: A Multi-Institutional Series - Erika Crosetti; Andrea Borello; Andy Bertolin; Izabela Costa Santos; Marco Fantini; Giulia Arrigoni; Ilaria Bertotto; Andrea Elio Sprio; Fernando Luiz Dias; Giuseppe Rizzotto; Giovanni Succo (Current Oncology)
Early-stage laryngeal cancer (T1-T2) is commonly treated with organ-preserving techniques such as transoral laser microsurgery (TOLMS) or radiation therapy (RT), both providing comparable oncological outcomes but differing in functional results. Local recurrence occurs in approximately 10% of cases, making salvage surgery a crucial therapeutic option. This multi-institutional study investigates the efficacy of open partial horizontal laryngectomy (OPHL) as a salvage treatment, following recurrent laryngeal squamous-cell carcinoma (LSCC) after failed TOLMS. This analysis includes 66 patients who underwent OPHL between 1995 and 2017, reporting favorable oncological outcomes with overall survival (OS) of 87.4%, disease-specific survival (DSS) of 93.4%, and disease-free survival (DFS) of 85.5%. A recurrence rate of 10.6% was observed post-salvage OPHL, with vascular invasion and advanced pathological staging identified as significant predictors of recurrence. OPHL emerged as an effective organ-preserving alternative to total laryngectomy (TL) in select patients, especially those with limited tumor spread and preserved laryngeal function. The study highlights the importance of careful patient selection and thorough preoperative assessment to improve outcomes, positioning OPHL as a key option in treating recurrent laryngeal cancer and offering oncological control while preserving laryngeal functions.